The Great Court of the Hall of Science (Arena Photo Post Card Co.)
This court covers an area of three acres. Here, visitors gather for festival ceremonies and other special events. Speakers address them from a uniquely constructed rostrum extending into the center of the court from the terrace. Within the huge steel frame behind the rostrum hangs the electrical chart which was used in demonstrating how the different Observatories made contact with the start Arcturus, when its rays turned on the lights of the Exposition.